Autoregressive Distributed Lag (ARDL) approach for re-testing the Fisher effect in Indonesia - Lilis Yuliati; Ananda Fauziah Mukti; Riniati (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2020)
This article discusses about re-testing the validity of the Fisher hypothesis in Indonesia. By using Autoregressive Distributed Lag (ARDL) approach, we will know if there is any causality between interest rate and inflation or not, for the long-term relationship. Interest rate divided into two main points, real interest rate and nominal interest rate. Hence, there are three main variables for this research, inflation, real interest rate and nominal interest rate. We applied the bound test to know cointegration between variables. The result shows that there is no evidence of long-term relationship and short term relationship between nominal interest rate and inflation in Indonesia.